Resilience programming among nongovernmental organizations: Lessons for policymakers - Frankenberger, Timothy R.; Constas, Mark A.; Nelson, Suzanne; Starr, Laurie (International Food Policy Research Institute, 2014)
This food policy report reviews resilience processes, activities, and outcomes by examining a number of case studies of initiatives by nongovernmental organizations (NGOs) to enhance resilience capacity, and draws implications for policymakers and other stakeholders looking to strengthen resilience.